2020
DOI: 10.51791/njap.v40i2.1251
|View full text |Cite
|
Sign up to set email alerts
|

Effects of varying levels of dietary palm oil in concentrate rations on dry matter intake, nutrients digestibility and nitrogen retention in Red Sokoto goats

Abstract: Twenty Red Sokoto bucks (average liveweight of 21.4±3.2 kg) were used to evaluate the effects of varying levels of palm oil (PO) in concentraterations on nutrients digestibility and nitrogen retention. Five iso-nitrogenous concentrate supplements (CP 160 g/kg concentrate) compounded with 0, 40, 80, 120 and 160 g palm oil/kg of concentrate, were used to supplement a basal diet of wooly finger grass (Digitaria smutsii, Stent) hay. The five supplements were designated as treatments 0-PO (control), 40-PO, 80-PO, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
(23 reference statements)
0
0
2
Order By: Relevance
“…However, increasing the level of concentrate supplementation did not affect the total DM intake of the animals fed the supplemented diets. In contrast to the current study, Otaru et al (2016) observed an increase in dry matter intake with increasing levels of concentrate supplements in the diet. The authors attributed the increased DMI to higher ingestion of protein and energy from the concentrate supplemented at 2.5% body weight, which, in synergy, facilitated rumen bacteria growth to enhance digestion and absorption by the ruminant.…”
Section: The Effect Of Concentrate Supplement On Dry Matter and Water...contrasting
confidence: 99%
See 1 more Smart Citation
“…However, increasing the level of concentrate supplementation did not affect the total DM intake of the animals fed the supplemented diets. In contrast to the current study, Otaru et al (2016) observed an increase in dry matter intake with increasing levels of concentrate supplements in the diet. The authors attributed the increased DMI to higher ingestion of protein and energy from the concentrate supplemented at 2.5% body weight, which, in synergy, facilitated rumen bacteria growth to enhance digestion and absorption by the ruminant.…”
Section: The Effect Of Concentrate Supplement On Dry Matter and Water...contrasting
confidence: 99%
“…Moreover, the effect of supplemental concentrate level on DMI demonstrated in this study was consistent with the findings of Mele et al (2008), who discovered that feeding increasing levels of concentrate to goats consuming a basal roughage diet did not influence dry matter intakes. The disparity between this study's findings and those of Otaru et al (2016) could be attributed to forage quality.…”
Section: The Effect Of Concentrate Supplement On Dry Matter and Water...contrasting
confidence: 90%